1993
DOI: 10.1152/ajplung.1993.264.2.l183
|View full text |Cite
|
Sign up to set email alerts
|

Tubule formation by human surface respiratory epithelial cells cultured in a three-dimensional collagen lattice

Abstract: Human surface respiratory epithelial (HSRE) cells from nasal polyps have been cultured within collagen lattices in a serum-free defined medium. Cell growth observed over a period of 12 days showed a population doubling time of 36 h. Under these culture conditions, we observed a contraction of the lattices. Phase-contrast light microscopy and transmission electron microscopy demonstrated that the HSRE cells formed tubular ductlike structures. Lumens formed by HSRE cells were surrounded by cuboidal-shaped polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…The death rates of infected target cells were estimated to be between 2.1 and 13.5 day Ϫ1 , higher than our estimate of 1.2 day Ϫ1 . The difference in the epithelial cell death rates could be due to the relatively high virus production value assigned in our study, which was chosen based on direct measurements from in vitro systems using cultured airway epithelial cells (6,27,57). Based on these estimates, we fixed virus production at 100 EID 50 ⅐ ml Ϫ1 ⅐ cell Ϫ1 ⅐ day Ϫ1 and estimated innate virus clearance (c V ) as 4.2 day Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
“…The death rates of infected target cells were estimated to be between 2.1 and 13.5 day Ϫ1 , higher than our estimate of 1.2 day Ϫ1 . The difference in the epithelial cell death rates could be due to the relatively high virus production value assigned in our study, which was chosen based on direct measurements from in vitro systems using cultured airway epithelial cells (6,27,57). Based on these estimates, we fixed virus production at 100 EID 50 ⅐ ml Ϫ1 ⅐ cell Ϫ1 ⅐ day Ϫ1 and estimated innate virus clearance (c V ) as 4.2 day Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive production of major gelatinase B and minor gelatinase A by HBECs may contribute to the basal remodeling of the subepithelial basal lamina as well as to the epithelial tubular morphogenesis possibly involved in the remodeling of bronchial mucosa following injury and inflammation (44). Indeed, several in vitro studies have shown that cultures of epithelial cells from different origins including mammary glands (45) and respiratory epithelium may organize into tubular structures (46). Extracellular matrix-degrading proteinases such as 72-kDa gelatinase have been shown to regulate mammary epithelial function during involution (47).…”
Section: Basal Expression Of Hbec Gelatinasesmentioning
confidence: 99%
“…Additionally, type IV collagen is the one of the more abundant ECM proteins in nasal epithelium (Benali, Tournier et al, 1993), suggesting that MMP-9 would be an effective enzyme for increasing permeability there. Our results showed that the 75 kDa CAT was transported into all the regions of brain within 15 min.…”
Section: Discussionmentioning
confidence: 99%